Qualitative study of the consequences of vaccine-induced immune thrombocytopenia and thrombosis: the experiences of family members - Paul Bennett (BMJ Open, 2023)
Objectives : To explore the experiences of family members of patients who died or survived following a diagnosis of vaccine-induced immune thrombocytopenia and thrombosis (VITT). Design; A semistructured qualitative study, conducted via Zoom. Setting: Participants discussed their experiences during hospitalisation and following discharge. Participants: Sixteen family members of patients with VITT (survivors=11; bereaved=5), recruited via a Facebook support group and advertising on Twitter. Results: Analysis identified two themes common to both groups of participants: the stress of hospitalisation and the experience of multiple losses. A third theme, living with VITT, was unique to the survivor group and a fourth, battling against the system, was predominantly reported by bereaved participants. Conclusion: This is a significantly challenged group of people, with multiple emotional, financial, social and psychological losses. These losses have been compounded by experiences of limited governmental and societal recognition of the problems they face.